A study on employee awareness towards ISO 9000 standards in improving service quality at DAHE Industries Malaysia Sdn. Bhd. / Siti Rauhana Ahmad - Ahmad, Siti Rauhana (Faculty of Business and Management, 2001)
The purpose of this study is to investigate the level of awareness of employees at DAHE Industries Sdn Bhd about ISO 9000 standards in improving their service quality. A total of 34 respondents were involved in this study , which constitutes 52% of the response rate . Chapter 4 of this report is particularly outline of the survey with regards to the finding and analysis of this study. In general ISO 9000 standards give benefits to the company such as greater customer loyalty, improvements in market share, greater productivity and cost reduction. From the findings and the data analysis, it can be concluded that majority of the respondents were aware about ISO 9000 standards. However, there are also a large number of respondents, who never attended seminars on ISO 9000 standards. The main reason is because most of them could get their knowledge about ISO 9000 standards from other sources such as articles and books. Most of the respondents also gave a positive perception on the benefits of implementing ISO 9000 standards for their company. It shows that the employees highly agree if the company implements the ISO 9000 standards. Employee should give full commitment to their company in order to improve the service quality of the company. Employees have to be more exposed to the ISO 9000 standards and the importance of it.